Using Narrative Approach for Anticipatory Grief Among Family Caregivers at Home - Toyama, Hiroko (Glob Qual Nurs Res, 2016)
Family caregivers of patients with terminal-stage cancer have numerous roles as caregivers, which can influence their anticipatory grief. The purpose of this study was to clarify how talking to family caregivers of patients with terminal illness using the narrative approach can influence such caregivers’ process of anticipatory grief. We conducted the narrative approach as an intervention with two family caregivers several times and qualitatively analyzed their narratives. The results indicated that these family caregivers had two primary roles—family member and caregiver—and that family caregivers felt trapped in their caregiver role. The narrative approach helped them transition into the role needed for coping with the loss.